Nomogram prediction model for lymph node metastasis after neoadjuvant chemoradiotherapy in rectal cancer - CAO Chenliang*，WANG Ling，SHI Haihua (Zhongguo linchuang yanjiu)
Objective To construct a nomogram prediction model for predicting lymph node metastasis in stage Ⅱ-Ⅲ rectal cancer patients after receiving neoadjuvant chemoradiotherapy（nCRT）based on LASSO regression ，and to evaluate its efficacy. Methods The clinical data of 150 patients admitted to Suzhou Municipal Hospital from September 2010 to December 2024 were included in this study. All patients received nRCT combined with total mesorectal excision. Data processing was conducted using R4.3.3 and SPSS 23.0 software. Initially，the LASSO regression method was employed to screen for key variables，followed by a multivariate logistic regression analysis to identify risk factors for lymph node metastasis after nCRT. A nomogram prediction model was then constructed，and its performance was comprehensively evaluated using methods such as the receiver operating characteristic（ROC ）curve.Results Four potential predictors were identified as independent risk factors，including age（ OR=2.949，95%CI：1.050-8.284），body mass index（BMI）（ OR=6.808，95%CI：2.772-16.724），post-neoadjuvant carcinoembryonic antigen（CEA）（ OR=2.376，95%CI：1.020-4.586），and yield pathologic T（ypT）stage（ OR=5.783，95%CI：1.894-17.655）（P<0.05）. The ROC curve area under the curve（AUC）predicted by this model for lymph node metastasis in rectal cancer patients was 0.843（95%CI：0.776-0.911）. Conclusion After nCRT，patients who were younger，had a higher BMI，had a CEA level>5 μg/L，and had deeper tumor infiltration should be vigilant for the risk of lymph node metastasis. The nomogram prediction model established based on these factors not only has high prediction accuracy but also possesses strong clinical application potential.